Influences of Plant Species, Season and Location on Leaf Endophytic Bacterial Communities of Non-Cultivated Plants. - Tao Ding; Ulrich Melcher (PLoS ONE)
Bacteria are known to be associated endophytically with plants. Research on endophytic bacteria has identified their importance in food safety, agricultural production and phytoremediation. However, the diversity of endophytic bacterial communities and the forces that shape their compositions in non-cultivated plants are largely uncharacterized. In this study, we explored the diversity, community structure, and dynamics of endophytic bacteria in different plant species in the Tallgrass Prairie Preserve of northern Oklahoma, USA. High throughput sequencing of amplified segments of bacterial rDNA from 81 samples collected at four sampling times from five plant species at four locations identified 335 distinct OTUs at 97% sequence similarity, representing 16 phyla. Proteobacteria was the dominant phylum in the communities, followed by the phyla Bacteriodetes and Actinobacteria. Bacteria from four classes of Proteobacteria were detected with Alphaproteobacteria as the dominant class. Analysis of molecular variance revealed that host plant species and collecting date had significant influences on the compositions of the leaf endophytic bacterial communities. The proportion of Alphaproteobacteria was much higher in the communities from Asclepias viridis than from other plant species and differed from month to month. The most dominant bacterial groups identified in LDA Effect Size analysis showed host-specific patterns, indicating mutual selection between host plants and endophytic bacteria and that leaf endophytic bacterial compositions were dynamic, varying with the host plant's growing season in three distinct patterns. In summary, next generation sequencing has revealed variations in the taxonomic compositions of leaf endophytic bacterial communities dependent primarily on the nature of the plant host species.